2008
DOI: 10.1002/pssc.200779122
|View full text |Cite
|
Sign up to set email alerts
|

Second‐harmonic generation from ZnO nanowires

Abstract: Optical second‐harmonic generation (SHG) from ZnO nanowires is investigated in the region around the band gap. Strong multiphoton excited luminescence and SHG appearing together in the spectra from wires are separated and the SHG part is compared to that of a bulk crystal. The spectrum of the effective second‐order nonlinear susceptibility of the nanowires is extracted from measured SHG intensity by taking into account linear optical propagation governed by effective refractive indices reflecting the volume fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 14 publications
3
25
1
Order By: Relevance
“…Regarding bulk crystals, the wavelengthdependence of their nonlinear susceptibilities have been scarcely studied and data are often limited to discrete wavelengths [7] due to the lack in the past of readily available tunable excitation sources and because of material transparency issues. Among spectrally resolved Second Harmonic (SH) studies, an increase in the susceptibility has been demonstrated so far for zinc-blende II-VI semiconductors [8], GaAs [9] and ZnO [10,11] when the SH frequency is tuned to the electronic transition energies. These studies provide experimental data for comparison with theoretical models which still need to be refined.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding bulk crystals, the wavelengthdependence of their nonlinear susceptibilities have been scarcely studied and data are often limited to discrete wavelengths [7] due to the lack in the past of readily available tunable excitation sources and because of material transparency issues. Among spectrally resolved Second Harmonic (SH) studies, an increase in the susceptibility has been demonstrated so far for zinc-blende II-VI semiconductors [8], GaAs [9] and ZnO [10,11] when the SH frequency is tuned to the electronic transition energies. These studies provide experimental data for comparison with theoretical models which still need to be refined.…”
Section: Introductionmentioning
confidence: 99%
“…The non-linear optical properties of ZnO nanowires have been studied extensively, and a large second-order optical non-linearity has been documented by near-field imaging in singe nanowires [11], by employing the maker fringes technique on an array of aligned nanowires [12], by two-photon absorption measurements on single nanowires [13], by comparing SHG spectra from bulk ZnO and a randomly oriented ensemble of ZnO nanowires [14], and by two-photon induced photo-luminescence measurements performed on both aligned arrays of nanowires and single nanowires [15]. ZnO thin films also possess a large second-order susceptibility [16][17][18] and could be used as an alternative to nanowires to facilitate circuit integration by e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is well‐known that the linear and nonlinear optical procedures, such as optical absorption and harmonic generation, are important and notable optical phenomena, especial in quantum‐confined systems and in the case of strong incident light intensity . Moreover, the optical nonlinearities in ZnO low‐dimensional quantum structures have been studied . For example, very strong second‐harmonic‐generation (pm/V) and third‐harmonic‐ generation (1018m 2 V −2 ) susceptibilities have been observed in ZnO thin film structures .…”
Section: Introductionmentioning
confidence: 99%